Pengaruh Bauran Pemasaran Terhadap Keputusan Pembelian Pada Ss Coffee Space Di Makassar - Dwi sieke Rustiray; Milka Pasulu; Andi Hendra Syam (Jurnal Online Manajemen ELPEI, 2021)
The purpose of this research was to determine the effect of the marketing mix on purchasing decisions at SS Coffee Space partially and simultaneously. The research method uses quantitative methods with descriptive and causal research types. In recent months in Indonesia there has been a phenomenon where many teenagers have opened coffee businesses. At least 30 teenagers who opened modern coffee businesses in various regions. Several teenagers opened coffee in the same area. One such area is the city of Makassar. Intense competition in the coffee industry makes each business actor try to build and maintain customer loyalty. To survive in the midst of intense competition, companies carry out strategies. One strategy that can be used to influence purchasing decisions is the marketing mix strategy. The population in this study were consumers who had made purchases at SS Coffee Space with a sample of 150 respondents. Sampling was carried out using a questionnaire method, namely the type of primary data. The data analysis technique uses simple linear analysis. The marketing mix at SS Coffee Space has a percentage value of 368.3%. The results of the R square test found that the marketing mix has an influence of 0.790. this states that the marketing mix affects purchase satisfaction by 79.0%, this proves that the effect of the marketing mix on purchase satisfaction is in the strong category. The remaining 21% is influenced by other variables that have not been studied in this study.